Club drugs Cosa sono e cosa fanno - Mannaioni, Pierfrancesco (Studi e saggi, 2008)
Club drugs is aimed not only at sector specialists but also at a broader public. It addresses the highly topical issue of the drugs and substances of abuse commonly used in social venues and clubs for recreational or socialising purposes. Garbed in a discursive and communicative language, albeit thoroughly supported by scientific evidence, the results of the research on the most widespread "recreational" drugs - ecstasy, GHB, Rohypnol, crack, cannabis and cocaine - are presented. The book takes its place within the debate on a social phenomenon in continual growth, replacing the Manicheism of prohibitionist and anti-prohibitionist positions with the most up-to-date results of scientific research.